Frequency of Microalbuminuria and Its Association with Hypertension, Obesity, and Smoking in Patients with Type 2 Diabetes Mellitus - Khan, Ali Khizar; Azam, Muhammad Bin; Riaz, Khadija; Maryam, Mubbashra; Ahmed Tarin, Siraj Munir (Biological and Clinical Sciences Research Journal, 2025)
Microalbuminuria (MA) is an early marker of diabetic kidney disease and clusters with cardiometabolic risks prevalent in Pakistan. Estimating the burden and identifying correlates among local patients with type 2 diabetes mellitus (T2DM) can guide targeted prevention efforts. Objective: To determine the frequency of MA and its association with hypertension, obesity, and smoking among adults with T2DM. Methods: We conducted a cross-sectional study of consecutively recruited adults with type 2 diabetes mellitus (T2DM) (aged 30–65 years; duration >2 years) attending the Department of Medicine at Ibn-e-Siena Hospital, Multan, Pakistan, over a six-month period (November 2023 to May 2024). The sample comprised 171 participants. MA was defined as a urine albumin-to-creatinine ratio (ACR) of 30–300 mg/g on an early-morning/spot urine sample. Prespecified correlates included hypertension (controlled vs uncontrolled), current smoking (≥10 cigarettes/day for ≥2 years), and obesity (BMI ≥30 kg/m²). Demographics, diabetes duration, and treatment (insulin ± oral agents vs oral agents only) were recorded. Bivariate associations were assessed using χ², t-tests, or Wilcoxon tests, as appropriate. Multivariable logistic regression estimated adjusted odds ratios (aORs) with 95% confidence intervals (CIs); model calibration was assessed by the Hosmer–Lemeshow test (p = 0.62). Two-sided p < 0.05 was considered statistically significant. Results: Mean age was 52.3 ± 8.5 years; 57.9% were men; mean BMI was 28.6 ± 4.2 kg/m²; 63.2% had hypertension, 26.9% smoked, and 33.9% were obese. MA prevalence was 29.8% (51/171). On bivariable analysis, MA increased with age (10.0% at 30–39 to 40.5% at 60–65; p = 0.010) and diabetes duration (14.5% at 2–5 years to 47.4% at >10 years; p < 0.001) and was higher in hypertensive vs non-hypertensive participants (37.0% vs 17.5%; p = 0.004), smokers vs non-smokers (45.7% vs 24.0%; p = 0.006), obese vs non-obese (41.4% vs 23.9%; p = 0.014), and those on insulin-based therapy vs oral agents only (44.4% vs 21.3%; p = 0.002). In multivariable models, independent predictors of MA were longer T2DM duration (per 5 years: aOR 1.64, 95% CI 1.25–2.17; p < 0.001), hypertension (aOR 2.14, 1.07–4.27; p = 0.032), current smoking (aOR 2.30, 1.17–4.53; p = 0.016), obesity (aOR 1.89, 1.01–3.53; p = 0.048), insulin-based therapy (aOR 2.25, 1.16–4.37; p = 0.017), and older age (per 5 years: aOR 1.18, 1.01–1.38; p = 0.036). Sex was not associated (aOR 1.31, 0.68–2.50; p = 0.41). Conclusion: Nearly one-third of Pakistani adults with T2DM had MA. Longer diabetes duration, hypertension, obesity, smoking, older age, and insulin-based therapy independently increased the odds of MA. Incorporating routine MA screening and intensifying control of modifiable risks, such as blood pressure, body weight, and tobacco use, should be prioritized within diabetes care pathways to mitigate kidney disease progression.